IRIIE2012 Poster: The Role of Tawhidic Paradigm in the Transformation of Management System - Sarif, Suhaimi Mhd; Ismail, Yusof (2012)

(untitled)
This poster explains the critical importance of Tawhidic paradigm in transforming a management system. It proposes a general model that may be adapted by any types of organizations – business, governmental, political, or social. The paper proposes basic components of the paradigm and illustrates the application of selected aspects of the components in a typical firm. The conceptual study discusses the major components of the Tawhidic paradigm (Unity of God) and provides illustrations that help link the spirit of Tawhid with management function: planning, organization, leading, and controlling. All of the managerial functions should ensure that they are integrated with the ethos of Tawhid which harmonize other worldly (Al-Akhirah) (the Hereafter) and the worldly (Al-Duniya). With this spiritual awareness the evolving and continuing management system will be achieving the firm’s mission and objectives by implementing mutually reinforcing values referred to as promotion of goodness (‘amr bil ma’aruf) and prevention of evil (nahi anil munkar). The proposed framework makes continuous learning both of the Deen and one’s career in an important prerequisite for the successful maintenance of a harmonized organization.